Paradoxical regulation of IGF2 in promoting lipid metabolism in adipose tissues - Caiping Zhou; Weiwei Gui; Weifen Zhu; Hanxin Zhao; Dingting Wu; Fang Wu; Gangliang Wang; Xihua Lin (Communications Biology)
Abstract Metabolic diseases such as diabetes, obesity, and dyslipidemia pose major public health challenges globally. While the insulin-like growth factor 2 (IGF2) gene is known to be involved in various physiological processes, its precise role in lipid metabolism is still not well understood. Here we show that IGF2 plays a crucial role in regulating lipid metabolism in adipose tissues and is linked to metabolic syndrome (MetS). Multiple SNP loci in the IGF2 gene were significantly associated with BMI, HbA1c, and diabetes. Insufficient or excessive expression of IGF2 was identified as a risk factor for hyperlipidemia, low HDL-c, and central obesity in MetS. Enhanced IGF2 expression stimulated adipogenesis and lipid accumulation, whereas IGF2 knockdown hindered lipolysis, exacerbating ectopic lipid accumulation and insulin resistance. Activation of the PI3K/Akt pathway through IGF1R in IGF2 excess or INSR in conditions of IGF2 scarcity, along with inhibition of AMPK, implies a common downstream process that favors lipid accumulation and metabolic reprogramming in adipocytes. This research provides valuable insights into the mechanisms underlying IGF2’s impact on lipid metabolism and has the potential to guide future therapeutic strategies for metabolic diseases.